2019
DOI: 10.5194/acp-19-9887-2019
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical aging of atmospherically reactive organic compounds involving brown carbon at the air–aqueous interface

Abstract: Abstract. Water-soluble brown carbon in the aqueous core of aerosol may play a role in the photochemical aging of organic film on the aerosol surface. To better understand the reactivity and photochemical aging processes of organic coating on the aqueous aerosol surface, we have simulated the photosensitized reaction of organic films made of several long-chain fatty acids in a Langmuir trough in the presence or absence of irradiation. Several chemicals (imidazole-2-carboxaldehyde and humic acid), PM2.5 samples… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 114 publications
0
8
0
Order By: Relevance
“…82 The reaction of oleic acid with other atmospheric oxidants has been studied at the air-water interface with nitrate radical, 83 OH radical, 84 nitrogen dioxide, 49 sulfur dioxide 85 and UV radiation via photosensitisation. [86][87][88]…”
Section: Bimolecular Kineticsmentioning
confidence: 99%
“…82 The reaction of oleic acid with other atmospheric oxidants has been studied at the air-water interface with nitrate radical, 83 OH radical, 84 nitrogen dioxide, 49 sulfur dioxide 85 and UV radiation via photosensitisation. [86][87][88]…”
Section: Bimolecular Kineticsmentioning
confidence: 99%
“…Imidazole derivatives such as IC are produced from glyoxal reactions in aqueous aerosol particles (see Refs 8,25 and references cited therein). IC has been the focus of many experimental studies 9,24,[26][27][28][29][30][31][32] but apart from some simple computations, 9 its photochemistry has not been investigated theoretically. Some measurements have revealed that IC can lead to significant SOA production, 29,30 although some others 31 suggest that more abundant photosensitizer species, such as humic-like substances, may contribute more significantly to SOA growth.…”
Section: Introductionmentioning
confidence: 99%
“…One such mechanism that has been recently proposed is photosensitization, ,, which involves a particle-phase, light-absorbing species promoting the oxidation of a volatile organic compound (VOC), which adds to SOA mass. Previously investigated photosensitizers include imidazole-2-carboxaldehyde, , non-phenolic aromatic carbonyls, , and humic-like substances (HULIS). , Photosensitization has also been investigated for its role in particle aging and sulfate formation …”
Section: Introductionmentioning
confidence: 99%